PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE DALAM UPAYA PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Tina Suci Susilawati; Ricki Yuliardi; Abdul Rosyid (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2017)
Application Of Cooperative Learning ModelType Think Talk Write In An Effort To Increase Mathematical Communication Skill.This study aims to examine the improvement of students' mathematicalcommunication skills with Think Talk Write model. This research involvesexperimental class and control class which is taken from class VII (Seven) SMPNegeri 1 Lebakwangi academic year 2016/2017. From the results of the pre-testknown that mean score of the control class was 9,53 while the experiment class is16,85. While the result of the post-test show that the mean of the control classes skorare 26,12 then the mean of the experiment classes score 29,75. The data that gettingfrom post-test doesn’t come from the normal distribution, so this dara was comparedby using Mann-Whitney (U) test for large samples. From the analyze, we know thatzcount = 0,43 dan ztable = 1,64. From both of data we know that 0,43 < 1,64. It meansthat after treatment the experiment classes student’s of mathematical communicationmore than control classes. The improvement of the mathematical communicationability of the classroom is not in addition to the result of the student responsequestionnaire, it is known that the students show neutral response to the learningmodel Think Talk Write.